SERAWAI TRIBE COMMUNITY'S EFFORTS TO BUILD FAMILY RESILIENCE THROUGH: the Tradition of Fighting for Girls from Maslahah Murlah's Perspective - Shiddiq, Akbar; Hakim, H. M. Aunul; Taklima, Musa; Miladiah, Vida Rofika (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
This study examines of the beterang tradition for girls in strengthening family resilience among the Serawai ethnic community through the perspective of maslahah mursalah. The study used a qualitative approach combining legal-sociological and normative methods. Data were gathered by observing, conducting detailed interviews, and reviewing documents from traditional leaders, religious people, parents, and young women. The findings indicate that the beterang tradition serves as a medium for internalizing religious, moral, and social values, contributing significantly to the psychological and spiritual readiness of young women for family life. It also plays a strategic role in preventing family conflicts, strengthening social relations, and fostering ethical awareness. From the perspective of maslahah mursalah, this tradition fulfills the principles of maqashid al-shari‘ah, particularly in safeguarding religion, life, intellect, lineage, and property, thus remaining relevant as a contextual model of family education based on Islamic values and local wisdom.